MEASURES TO MAINTAIN SANITARY AND ECOLOGICAL ORDER IN THE TERRITORY OF THE NORTH CAUCASIAN FEDERAL DISTRICT - Olga Grigoryevna Fabrikantova; Elena Gennad'evna Brezhneva (Современная наука и инновации)
Considers the problems of municipalities, and especially the largest of them, associated with excessive concentration on a relatively small area population, transport and industrial enterprises, with the formation of anthropogenic landscapes, very far from a state of ecological balance.